New Severn Watercolours from the Voyage to Italy with Keats. Issue 2 (July 2016) - Scott, Grant F.
Abstract : The rediscovery of three of Joseph Severn's watercolours from his 1820 journey to Italy with Keats provides an important visual counterpart to his famous journal-letters. Together with a number of other sketches he made onboard the Maria Crowther, these works offer us a new perspective on the voyage. The watercolours form part of the Charles Lee Smith Papers at Wake Forest University, an archive that also contains other significant Keatsiana, including an inventory of Keats manuscripts and relics which were found in Severn's room after his death. The provenance of the watercolours lends us a fascinating glimpse into the lives of Lady Maureen Watson and her daughters as they flee the threat of Hitler's invasion and try to establish a new life in North Carolina.